DNA structure and function - Sinden, Richard R. (Academic Press, 1994)
DNA Structure and Function, a timely and comprehensive resource, is intended for any student or scientist interested in DNA structure and its biological implications. The book provides a simple yet comprehensive introduction to nearly all aspects of DNA structure. It also explains current ideas on the biological significance of classic and alternative DNA conformations. Suitable for graduate courses on DNA structure and nucleic acids, the text is also excellent supplemental reading for courses in general biochemistry, molecular biology, and genetics. Special Features * Explains basic DNA Structure and function clearly and simply * Contains up-to-date coverage of cruciforms, Z-DNA, triplex DNA, and other DNA conformations * Discusses DNA-protein interactions, chromosomal organization, and biological implications of structure * Highlights key experiments and ideas within boxed sections * Illustrated with 150 diagrams and figures that convey structural and experimental concepts.